Prevalence and Clinical Correlates of Self-Harm Behaviors in Gilles de la Tourette Syndrome - Szejko, Natalia; Jakubczyk, Andrzej; Janik, Piotr (Frontiers in Psychiatry, 2019)
Major symptoms of Gilles de la Tourette’s syndrome (GTS) are tics, but in 90% of cases, psychiatric comorbidities occur. Self-harm behaviours (SHB) could result from deliberate action and unintentional injury from tics. The aim of our study was to investigate the prevalence and clinical correlates of SHB in a Polish cohort of GTS patients. We examined 165 consecutive GTS patients aged 5–50 years old (75.8% males). The patients were evaluated for GTS and co-morbid mental disorders according to the DSM-IV-TR. SHB was diagnosed during the interview. To determine a direct relationship between SHB and clinical variables, we conducted two analyses, at the time of evaluation and lifetime. We also compared the group of children and adults with SHB and tried to distinguish between deliberate (non-tic related SHB) and accidental (tic related SHB). Lifetime SHB was reported by 65 patients (39.4%). In 30 of the patients (46.2%), SHB was evaluated as mild, in 26 (40%) as moderate and in only nine (13.9%) cases as severe. In the multivariable analysis for the predictor of lifetime SHB, attention deficit hyperactivity disorder (ADHD; p = 0.016) and obsessive-compulsive disorder (OCD; p = 0.042) were determined as risk factors, while for current SHB only tic severity (p < 0.0001) was statistically significant. When comparing predictors of SHB for children and adults, tic severity was determined as predictor for lifetime SHB in children (p<0.0001), while the anxiety disorder was associated with the lifetime SHB in adults (p=0.05). Similarly, tic severity was a predictor of current SHB in children group (p=0.001), but this was not confirmed for adults. The group of patients with tic related and non-tic related SHB did not differ. SHB appears mostly in children and adolescents, and rarely begins in adulthood. SHB is associated mainly with tic severity, OCD and ADHD. Clinical correlates of SHB are age-related and differ at different point of life. Tic severity is the main factor associated with SHB in children. In group of adults, anxiety disorder and other psychiatric comorbidities may play the most important role.